Criminal Liability for the Infringement of IP Rights: Ukraine and the European Court of Human Rights Case Law - Войтович, Павло Петрович; Войтович, П. П.; Войтович, Павел Петрович; Voitovych, Pavlo P.; Еннан, Руслан Євгенович; Еннан, Р. Є.; Эннан, Руслан Евгеньевич; Ennan, Ruslan Ye.; Волошина, Владлена Костянтинівна; Волошина, Владлена Константиновна; Волошина, В. К.; Voloshyna, Vladlena K. (Kiev : VD “Dakor”, 2020)
Summary: 1. Introduction. – 2. Legal Regulation and Its Gaps. – 3. ECtHR Case Law and Its Impact on the Ukrainian Practice. – 4. Concluding Remarks. Ukraine’s national legislation and the European Court of Human Rights’s case-law outline Сopyright protection. Many cases exist where the public significance and damage from copyright infringement entails holding the guilty person criminally responsible for the transgression. Given copyright infringement cases do not reflect a predominant concern over other crimes, a structured criminal prosecution mechanism does not exist. Thus, the European Court of Human Rights’ legal positions and instructions intend to eliminate gaps legally regulating criminal liability for copyright infringement. Hence, the legal regulation, its gaps and ECHR case law impacts on Ukrainian practice were analysed. This structure enabled proposing steps for improving legally regulating criminal liability for copyright infringement in Ukraine.

Національне законодавство України та практика Європейського суду з прав людини окреслюють захист авторських прав. Існує багато випадків, коли суспільне значення та шкода від порушення авторських прав тягнуть за собою притягнення винної особи до кримінальної відповідальності за проступок. Враховуючи, що справи про порушення авторських прав не відображають переважну стурбованість іншими злочинами, структурованого механізму кримінального переслідування не існує. Таким чином, правові позиції та інструкції Європейського суду з прав людини мають на меті усунути прогалини, що регулюють законодавчо кримінальну відповідальність за порушення авторських прав. Отже, було проаналізовано правове регулювання, його прогалини та вплив судової практики ЄСПЛ на українську практику. Ця структура дозволила запропонувати кроки для вдосконалення законодавчого регулювання кримінальної відповідальності за авторське право в Україні.

Национальное законодательство Украины и прецедентная практика Европейского суда по правам человека определяют защиту авторских прав. Существует множество случаев, когда общественная значимость и ущерб от нарушения авторских прав влекут за собой привлечение виновного к уголовной ответственности за нарушение. Поскольку дела о нарушении авторских прав не отражают преобладающую озабоченность по поводу других преступлений, структурированного механизма уголовного преследования не существует. Таким образом, правовые позиции и инструкции Европейского суда по правам человека направлены на устранение пробелов, законодательно регулирующих уголовную ответственность за нарушение авторских прав. Таким образом, было проанализировано правовое регулирование, его пробелы и влияние судебной практики ЕСПЧ на украинскую практику. Такая структура позволила предложить шаги по совершенствованию законодательного регулирования уголовной ответственности за нарушение авторских прав в Украине.
Voitovych P. Criminal Liability for the Infringement of IP Rights: Ukraine and the European Court of Human Rights Case Law / P. Voitovych, R. Ennan, V. Voloshyna // Access to Justice in Eastern Europe. – V. 4(8). – Kiev : VD “Dakor”, 2020. – P. 291-297.
Keywords: author’s rights protection; criminal proceedings; ECtHR case law; захист авторських прав; кримінальне провадження; судова практика ЄСПЛ; защита авторских прав; уголовное производство; судебная практика ЕСПЧ; Research Subject Categories::LAW/JURISPRUDENCE